PENGARUH KUALITAS PELAYANAN DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PADA STUDIO SUN FOTO DI JAKARTA PUSAT - Helmi Al Hanif, Ahmad; Tika Kristina Hartuti, Elizabeth (Journal of Research and Publication Innovation, 2024)
This study aims to determine how the influence of Service Quality and Sales Promotion on Purchase Decisions at Sun Foto Studio Central Jakarta both partially and simultaneously. This research method uses a nonprobability sampling technique where samples are taken by chance, with a sample size of 100 respondents. Data collection techniques using questionnaires, and data analysis techniques are validity tests, reliability tests, simple linear analysis, multiple linear, correlation coefficients, determination coefficients, and hypothesis tests. The results of this study indicate that there is a significant influence between Service Quality and Sales Promotion simultaneously on Purchase Decisions at Sun Foto Studio Central Jakarta. The results of this study indicate that there is a significant influence between Service Quality and Sales Promotion simultaneously on Purchase Decisions at Sun Foto Studio Central Jakarta. This can be seen from the value of the regression equation Y = 6.243 + 0.231X1 + 0.595X2, which means that changes in Service Quality go in two directions with changes in Product Completeness. The multiple correlation coefficient value obtained is 0.854, meaning that the variables Service Quality and Sales Promotion have a strong relationship to Purchase Decisions. The coefficient of determination or contribution has an influence of 0.730 or 73.0% while the remaining 27.0% is influenced by other factors. Simultaneous hypothesis testing obtained a value of Fcount> Ftable or 130.855> 3.09, meaning that there is a significant influence between Service Quality and Sales Promotion on Purchasing Decisions at Sun Foto Studio Central Jakarta. Keywords: Service Quality, Sales Promotion, Purchasing Decisions